2017
DOI: 10.1111/cid.12562
|View full text |Cite
|
Sign up to set email alerts
|

Histological evaluations and inflammatory responses of different dental implant abutment materials: A human histology pilot study

Abstract: The tissue around the gold alloy abutments resulted in worse attachment conditions compared with the titanium and zirconia abutments. Inflammation tended to be higher in the tissue around the gold alloy abutments than the titanium and zirconia abutments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…However, the expression was observed only in the bottom part of the epithelium, towards the Pt-Au alloy, which indicates weaker adhesion to the epithelium to the Pt-Au alloy compared to the titanium and zirconia. This may lead to the result of soft/hard tissue apical shift, which has been reported previously [30,32].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, the expression was observed only in the bottom part of the epithelium, towards the Pt-Au alloy, which indicates weaker adhesion to the epithelium to the Pt-Au alloy compared to the titanium and zirconia. This may lead to the result of soft/hard tissue apical shift, which has been reported previously [30,32].…”
Section: Discussionmentioning
confidence: 78%
“…A previous study found that the tissues around the gold alloy abutment showed a more negative reaction than titanium and zirconia abutments. The Pt-Au alloy was demonstrated to have less attachment resistance and a higher inflammatory response compared with titanium and zirconia abutments [30].…”
Section: Discussionmentioning
confidence: 99%
“…This study is designed to directly analyse, in a human model, different materials used as supragingival components in daily implant dentistry. Though a few clinical studies have attempted to test some of the materials used (mainly titanium and zirconia) [ 10 , 12 , 29 ], the main limitations of prior studies is that they focused on one or two materials and/or the study design was not a randomized clinical trial and/or the analyses performed did not allow for the direct observation of the interface between the abutment material and soft tissues (i.e. instead of histology, other surrogate outcomes have been used).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that gold alloy abutment demonstrates a poor attachment to soft tissue compared with titanium and zirconia abutments. Moreover, inflammatory extent and inflammatory cells in the soft tissue, around the gold alloy abutment, were significantly higher than those around titanium and zirconia abutments 16 . However, the characteristics of inflammatory cells around different abutment types are not fully clarified.…”
Section: Introductionmentioning
confidence: 93%